GENERASI KEDUA DIGITAL NATIVE: JANUS FACE MEDIA SOSIAL DAN ANOMALI KOMUNIKASI - Matang, Matang; Suryadi, Karim; Darmawan, Cecep; Anggraeni, Leni; Riyanti, Dwi; Hudi, Ilham (Master of Communication Science Program, Universitas Diponegoro, 2023)
Today's students are understood as second generation digital natives (GDN-2) who are close and accustomed to using social media. Previous research explains digital natives in general, the role of social media in digital natives' daily lives. This study focuses on looking at the janus face of social media in GDN-2, the role of the family and their participation in social media. 308 students were willing to fill out a questionnaire as initial data, then in-depth interviews were conducted (N= 31). The research results show that the benefits of social media for GDN-2 are to share information and opinions, reach consumers and add business ideas, a place to learn and reference material, update information, and build relationships. Social media is detrimental to work and main activities, addiction, wasted time, lazing, having to pay for the internet, and false information. There is a family communication anomaly, parents do not have social media but give advice to their GDN-2 children to use social media wisely. This is then reflected in GDN-2's participation on social media. They are careful about spreading information that is not necessarily true, posting and commenting carefully.